Reports from the Field: Harnessing OER to Develop Teachers: The Guyana Experience - Neil Butcher (Commonwealth of Learning, 2014)
The Ministry of Education in Guyana has prioritised increasing the number of qualified teachers by providing opportunities to both pre- and in-service teachers to gain relevant qualifications. This paper describes the process used to redesign the teacher training curriculum in Guyana to achieve the goals of a newly-developed ICT Professional Development Strategy. The UNESCO ICT Competency Framework for Teachers (CFT) was central to the redesign process, and was used to review and reorganize the national teacher education curriculum aimed at pre-service teachers. The framework also influenced plans to provide professional development for in-service teachers, and influenced the selection of Open Education Resources (OER) used to develop a new learning environment and the accompanying learning materials for the teaching of ICT in Education. One of the significant lessons learned during this process is that people rather than technology are crucial to transformation. It is essential to have leadership support at the highest levels but also committed champions at all other levels. The process called for the inclusion of local stakeholders who understood and knew how to respond to contextual constraints. Moreover, the process benefited from the use of existing frameworks and the use of cost effective OER to develop the course materials.